Anti-apoptotic effects of novel phenolic antioxidant isolated from the Pacific oyster (Crassostrea gigas) on cultured human hepatocytes under oxidative stress. (1st June 2015) - Fuda, Hirotoshi; Watanabe, Mitsugu; Hui, Shu-Ping; Joko, Sae; Okabe, Hiroaki; Jin, Shigeki; Takeda, Seiji; Miki, Emiko; Watanabe, Takayuki; Chiba, Hitoshi
Highlights: An antioxidant of DHMBA was isolated from Pacific oyster. DHMBA showed no cytotoxicity (assessed by cell viability and transaminase release). In AAPH, DHMBA improved cell viability, whereas chlorogenic acid had no effect. DHMBA inhibited apoptosis and necrosis, whereas chlorogenic acid was ineffective. DHMBA is a potent antioxidant, protecting hepatocytes from oxidative stress. Abstract: The antioxidant, and hepatoprotective properties of 3, 5-dihydroxy-4-methoxybenzyl alcohol (DHMBA), a natural phenolic antioxidant isolated from the Pacific oyster, were defined using cultured human hepatocyte-derived cells (C3A). DHMBA showed no cytotoxicity at 62.5–500 μM, as well as chlorogenic acid (CGA), vitamin C, and vitamin E. However, butylated hydroxytoluene, eicosapentaenoic acid, docosahexaenoic acid and catechin reduced cell viability. In the presence of the prooxidant 2, 2′-azobis(2-amidinopropane) dihydrochloride (AAPH), DHMBA at 125–500 μM improved cell viability, whereas CGA had no effect. DNA ladder formation and flow-cytometric studies indicated that DHMBA inhibited AAPH-induced apoptosis and necrosis. CGA was ineffective. Thus, DHMBA is a novel, potent antioxidant, effectively protecting cultured hepatocytes from apoptosis and necrosis caused by oxidative stress. Additionally, the concentration of DHMBA was determined by mass spectrometry to be 24.4 μmol/kg wet oyster meat, and three polyphenols (gentisic acid, daidzein, and matairesinol) were newly identified in the oyster extracts.